GENERATION OF DECELERATION PULSES OF THE TROLLEY IN CHILD RESTRAINT SYSTEMS’ DYNAMIC TESTS BASED ON SIMULATIONS AND EXPERIMENTAL VALIDATIONS - ZHE WEI (Journal of Engineering Studies and Research)
As one of devices for passive safety, child restraint system remains a positive factor in securing the safety of child occupants in vehicles’ collisions. Generation of deceleration pulses is essential for dynamic tests conducted to assess the safety performance according to many regulations such as UN Regulation No. 44. It deserves research on how to generate the qualified pulses conveniently and with low cost. A new method of convenience using steel pipes or tubes is recommended after all the factors influencing the deceleration being ascertained. Varied combinations of parameters make it possible and easy to optimize the deceleration pulses.